2013
DOI: 10.1089/jop.2012.0078
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Artificial Tear Solution AffectsIn Vitro Pseudomonas aeruginosaBiofilm Formation on Silicone Hydrogel Lens

Abstract: P. aeruginosa biofilm formation on silicone hydrogel contact lens was affected by the composition of artificial tears. A higher concentration of HA and addition of benzalkonium chloride or dextran in artificial tears were helpful to prevent P. aeruginosa biofilm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Not only must they provide moisture to the injury, but also gel formulation must maintain drug stability during shelf time as well as an appropriate release during their administration. Several works have demonstrated that during hydrogel formulation, different excipients have variations in drug release . With regards to chemical stability, SOSs and chlorine can be exhausted into hydrogel because their high reactivity ; this idea is supported by our results because chlorine containing and SOSs were less effective against biofilm formation and elimination than DADS‐M or biguanide.…”
Section: Discussionsupporting
confidence: 77%
“…Not only must they provide moisture to the injury, but also gel formulation must maintain drug stability during shelf time as well as an appropriate release during their administration. Several works have demonstrated that during hydrogel formulation, different excipients have variations in drug release . With regards to chemical stability, SOSs and chlorine can be exhausted into hydrogel because their high reactivity ; this idea is supported by our results because chlorine containing and SOSs were less effective against biofilm formation and elimination than DADS‐M or biguanide.…”
Section: Discussionsupporting
confidence: 77%
“…Costagliola et al (45) found that staphylococci and streptococci were obtained low-molecular weight sugars that could be used as nutrients by producing hyaluronidase in the presence of HA. Some bacteria such as Pseudomonas aeruginosa did not have the ability to produce hyaluronidase, thus limiting the benefit of sodium hyaluronate to them (46,47). However, these results are not based on a complete microbiome, and therefore cannot explain whether this phenomenon occurs in the ocular surface microbiome.…”
Section: Discussionmentioning
confidence: 99%